ZAHIRIDDIN MUHAMMAD BABUR'S PRINCIPLES OF JUSTICE AND RULE OF LAW IN PUBLIC ADMINISTRATION - Buxarov Sherali (Web of Journals Publishing, 2025)
This article presents information on the principles of justice and the rule of law in public administration of Zahiriddin Muhammad Babur.
Keywords: governance, law, rule of law, state, justice, principle.